2020
DOI: 10.31629/marinade.v3i02.3404
|View full text |Cite
|
Sign up to set email alerts
|

KARAKTERISTIK ASAM AMINO DAN ASAM LEMAK BEKASAM KERANG BULU (Anadara antiquate) DI DESA BENAN KABUPATEN LINGGA

Abstract: Formation of feather shells (Anadara antiquata) which has been carried out the characteristics of amino acids and fatty acids obtained the highest amino acid yield is Arginine 10293.28, and the lowest histidine is 136.91. The highest saturated fatty acid is palmitic which is 1.20 and the lowest lauric acid is 0.09, the highest monounsaturated fatty acid is glutamic acid 17257.96, and the lowest is alanine 312.56, the highest polyunsaturated fatty acid is linoleic 0.58, linolenic acid 0.58, and the lowest arach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
2
0
3
Order By: Relevance
“…With the help of the cyclooxygenase enzyme, arachidonic acid is converted to prostaglandin-type eucosanoids and their derivatives (prostacyclin and thromboxane). Prostacyclin (PGI2) functions to inhibit blood clotting and facilitate blood flow, while thromboxane (TXA2) formed in platelets causes blood pieces to coalesce and clot [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…With the help of the cyclooxygenase enzyme, arachidonic acid is converted to prostaglandin-type eucosanoids and their derivatives (prostacyclin and thromboxane). Prostacyclin (PGI2) functions to inhibit blood clotting and facilitate blood flow, while thromboxane (TXA2) formed in platelets causes blood pieces to coalesce and clot [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The highest content of fresh soft shell crab was leucine (9.242%) and arginine (9.242%). Study on shellfish [21], reported that arginine is one of the compounds that can increase the salty and sweet taste of seafood such as crab and scallops. Study on pasteurized blue crab (Callinectes sapidus) meat [22] showed that lysine and leucine in boiled crab were 4.27% and 4.82%, respectively.…”
Section: Amino Acid Profilementioning
confidence: 99%
“…Pratama et al (2018) mengungkapkan bahwa apabila kandungan produk berada di atas ambang rasa, maka asam glutamat dapat berkontribusi pada rasa umami. Putra et al (2020) menjelaskan bahwa asam glutamat bermanfaat untuk meningkatkan kesehatan mental, dan mengurangi depresi serta mempercepat penyembuhan luka usus. Sumber alami asam glutamat yaitu makanan yang kaya protein seperti daging, makanan yang berasal dari laut, daging rebus (kaldu), dan kecap.…”
unclassified
“…Asam amino tertinggi kedua pada kolagen kulit ikan payus P3 yaitu asam aspartat sebesar 6,41%. Menurut Putra et al (2020), produksi urea, prekursor glukonik dan prekursor pirimidin, melibatkan komponen asam aspartat. Asam aspartat juga efektif dalam mengurangi kelelahan yang berkepanjangan.…”
unclassified
See 1 more Smart Citation